Gate‐Controlled Field Emission Current from MoS2 Nanosheets. (28th December 2020) - Pelella, Aniello; Grillo, Alessandro; Urban, Francesca; Giubileo, Filippo; Passacantando, Maurizio; Pollmann, Erik; Sleziona, Stephan; Schleberger, Marika; Di Bartolomeo, Antonio
Abstract: Monolayer molybdenum disulfide (MoS2 ) nanosheets, obtained via chemical vapor deposition onto SiO2 /Si substrates, are exploited to fabricate field‐effect transistors with n‐type conduction, high on/off ratio, steep subthreshold slope, and good mobility. The transistor channel conductance increases with the reducing air pressure due to oxygen and water desorption. Local field emission measurements from the edges of the MoS2 nanosheets are performed in high vacuum using a tip‐shaped anode. It is demonstrated that the voltage applied to the Si substrate back‐gate modulates the field emission current. Such a finding, that it is attributed to gate‐bias lowering of the MoS2 electron affinity, enables a new field‐effect transistor based on field emission. Abstract : A field‐effect transistor based on the modulation of the field emission current from the edge of monolayer MoS2 flakes is demonstrated. The field emission is facilitated by the intrinsic n‐type doping of MoS2 in high‐vacuum and is enhanced by a positive gate voltage that lowers the barrier for electron emission.